2013
DOI: 10.1002/mus.23858
|View full text |Cite
|
Sign up to set email alerts
|

Suramin attenuates dystrophin‐deficient cardiomyopathy in the mdx mouse model of duchenne muscular dystrophy

Abstract: These findings suggest that suramin may be a new adjunctive therapy to help improve cardiomyopathy in DMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Intraperitoneal injection of suramin in 6-month old mdx mice has been shown to increase MMP-2 and MMP-9 activity 96 , decrease creatine kinase, and to attenuate fibrosis in skeletal muscle, but not cardiac muscle 97 . In 8-month old mdx mice, however, suramin did improve cardiomyopathy and decrease myocardial fibrosis, inflammation, and myonecrosis 98 . Imatinib mesylate inhibited TFG-β pro-fibrogenic activity, decreased creatine kinase 99 , reduced fibrosis, and improve hind limb grip strength 100 in mdx mice.…”
Section: Drugs Targeting Fibrosismentioning
confidence: 81%
“…Intraperitoneal injection of suramin in 6-month old mdx mice has been shown to increase MMP-2 and MMP-9 activity 96 , decrease creatine kinase, and to attenuate fibrosis in skeletal muscle, but not cardiac muscle 97 . In 8-month old mdx mice, however, suramin did improve cardiomyopathy and decrease myocardial fibrosis, inflammation, and myonecrosis 98 . Imatinib mesylate inhibited TFG-β pro-fibrogenic activity, decreased creatine kinase 99 , reduced fibrosis, and improve hind limb grip strength 100 in mdx mice.…”
Section: Drugs Targeting Fibrosismentioning
confidence: 81%
“…The dosage of suramin (60 mg/kg twice weekly i.p.) was selected according to previous studies that effectively reduce myocardial fibrosis, inflammation, and myonecrosis in the mdx mouse model of Duchenne muscular dystrophy [ 28 , 29 , 30 ]. As shown in Figure 2 B and Supplementary Table S1 , the suramin-treated Pkd1 -miR Tg mice tended to have reduced kidney weights compared with saline-treated mutant mice, but the kidney-to-body weight ratios were not significantly different between the control and treatment groups ( Figure 2 C), possibly due to lower body weights found in the suramin-treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that suramin may induce phospholipidosis via the inhibition of lysosomal phospholipase A2 [ 51 ]. The dose of suramin used in the current study is still within the non-cytotoxic concentration range according to previous studies in mouse models of cardiac fibrosis and lung injury [ 28 , 29 , 30 ]. Although further studies using other animal models for PKD and different dosing schedules are needed to confirm our results, our findings raised an important safety concern about using suramin in the setting of PKD due to drug-induced kidney injury and lysosomal damage.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding clinical trials were terminated. Suramin is a TGF-β inhibitor that has shown antifibrotic function in mdx mice ( De Oliveira Moreira et al, 2013 ). The treatment of Suramin reduces the level of creatine kinase and attenuates fibrosis in skeletal muscles in mdx mice ( De Oliveira Moreira et al, 2013 , 2017 ).…”
Section: Therapeutic Strategies Targeting the Secondary Downstream Pathological Mechanismsmentioning
confidence: 99%
“…Suramin is a TGF-β inhibitor that has shown antifibrotic function in mdx mice ( De Oliveira Moreira et al, 2013 ). The treatment of Suramin reduces the level of creatine kinase and attenuates fibrosis in skeletal muscles in mdx mice ( De Oliveira Moreira et al, 2013 , 2017 ). Besides, Suramin can protect muscles against exercise-induced damage in mdx mice ( Taniguti et al, 2011 ).…”
Section: Therapeutic Strategies Targeting the Secondary Downstream Pathological Mechanismsmentioning
confidence: 99%